2014
DOI: 10.1021/am503731h
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Simultaneous Substitution of Y and Ta on the Stabilization of Cubic Phase, Microstructure, and Li+ Conductivity of Li7La3Zr2O12 Lithium Garnet

Abstract: Garnet-type lithium stuffed oxide Li7La3Zr2O12 (LLZ) in the cubic phase has received significant attention because of its high Li(+) conductivity at room temperature and excellent stability against lithium metal anodes. In addition to the high Li(+) conductivity, the dense microstructure is also a critical issue for the successful application of LLZ as a solid electrolyte membrane in all-solid-state lithium and lithium-air batteries. The stabilization of LLZ in the cubic phase with dopants indicated a reductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
66
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(69 citation statements)
references
References 69 publications
2
66
0
1
Order By: Relevance
“…Additional information regarding the phase composition and structure of LS-LLZA was obtained using Raman spectroscopy and the recorded Raman spectra of LS-LLZA and bare LLZA are both shown inFigure S3. The Raman modes of the collected spectrum (LS-LLZA) matches well with the reported Raman spectrum of cubic garnet phase34 which confirms that LS-LLZA after heat treatment at 300 °C have the single phase of cubic garnet structures.The effect of Li2SiO3 as a buffer layer between NMC and LLZA was qualitatively assessed by simple peel-off experiment (adherence test) and from cross-sectional SEM images. For the peeloff experiment, adhesive tape was stuck with NMC and then peeled from the surface of NMC coated over pristine LLZA and LS-LLZA.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…Additional information regarding the phase composition and structure of LS-LLZA was obtained using Raman spectroscopy and the recorded Raman spectra of LS-LLZA and bare LLZA are both shown inFigure S3. The Raman modes of the collected spectrum (LS-LLZA) matches well with the reported Raman spectrum of cubic garnet phase34 which confirms that LS-LLZA after heat treatment at 300 °C have the single phase of cubic garnet structures.The effect of Li2SiO3 as a buffer layer between NMC and LLZA was qualitatively assessed by simple peel-off experiment (adherence test) and from cross-sectional SEM images. For the peeloff experiment, adhesive tape was stuck with NMC and then peeled from the surface of NMC coated over pristine LLZA and LS-LLZA.…”
supporting
confidence: 81%
“…Earlier Raman studies on lithium garnets suggested that the Raman bands observed between 100 and 150 cm -1 corresponds to La cation, the broad and fairly overlapping Raman band observed between 200 and 500 cm -1 corresponds to the internal modes of LiO6 and LiO4 and is due to the dynamic disorder of highly mobile lithium ion. [34][35][36] The impedance data was fitted with the equivalent circuit shown as inset in Figure 1c. From the fitting result the semicircle at high-frequency regime seems to be mainly related to bulk response and the grain boundary contribution appears to be negligible.…”
Section: Characterization Of Llzamentioning
confidence: 99%
“…[5][6][7][8] Recent reports reveal that doping with elements such as Ga 3+ and Ta 5+ can improve its room temperature conductivity to 0.4∼1.0 × 10 −3 S cm −1 .…”
mentioning
confidence: 99%
“…41 This verified the structure model of Li 6 CaLa 2 Nb 2 O 12 in this work. The two bands at ~ 121 and 158 cm −1 may reveal important information for the dodecahedral site, since they are arising from LaO 8 and CaO 8 vibrations, 42 respectively. Noteworthy is that the two modes occur at lower frequencies than those of YO 8 in YAG, which implies that Li 6 CaLa 2 Nb 2 O 12 garnet would have a lower probability of multiphonon relaxation and is better suited for efficient luminescence of rare-earth activators.…”
Section: Characterizationsmentioning
confidence: 99%